ANALISIS PENGARUH BRISK WALKING EXERCISE TERHADAP TEKANAN DARAH PADA PASIEN HIPERTENSI DI KLINIK PRATAMA LANTAMAL II PADANG TAHUN 2025 - Clara Nadia; Monna Widyastuti; Dewi Susilaningsih; Meldawati Meldawati (Ensiklopedia of Journal, 2026)
The Padang City Central Statistics Agency stated that the number of hypertension cases recorded in 2022 will be 47,902 cases. The incidence of hypertension at the Pratama Lantamal II Clinic in Padang always increases every year. Management of hypertension is carried out using pharmacological and non-pharmacological techniques. Non-pharmacological management can be done by giving brisk walking exercises. This study aims to determine the effect of brisk walking exercise on blood pressure in hypertensive patients at the Pratama Lantamal II Clinic in Padang. This type of research is quantitative with a quasi-experimental design with a one group pretest-posttest design. This research was carried out from October 2024 to February 2025 at the Pratama Lantamal II Clinic in Padang. The population of this study was all hypertensive patients undergoing treatment during the period October 2024 to February 2025, with a total of 48 people and a research sample of 10 people. The sampling technique used was purposive sampling technique. Data processing is carried out by editing, entry and cleaning. Analysis uses a paired sample t-test. The results of the research showed that the average systole before being given brisk walking exercise was 154.5 mmHg with a standard deviation of 5.50252 and the average value of diastole before being given brisk walking exercise was 96.5 mmHg with a standard deviation of 4.11636 and the average value of systole after being given brisk walking exercise was 147.5 mmHg with a standard deviation of 3.53553 and the average value of diastole after being given brisk walking exercise was 89 mmHg with a standard deviation of 2.10819. Based on statistical tests, it was found that a p-value of 0.000 showed the effect of brisk walking exercise on blood pressure in hypertensive patients at the Pratama Lantamal II Clinic in Padang in 2025. It is hoped that the leadership of Pratama Lantamal II Padang Clinic will be able to hold brisk walking exercise as part of non-pharmacological therapy for hypertension patients and can provide health education regarding brisk walking exerciseKeywords : blood pressure, brisk walking exercise, hypertension